UNVEILING TOURISM POTENTIAL FOR SUSTAINABLE ECONOMIC DEVELOPMENT IN ALAMENDAH TOURISM VILLAGE - Fatin, Anisya; Askhiya, Ghina; Rosyifa, Mutia; Andari, Rini; Khosihan, Aan (Penerbit Lafadz Jaya, 2024)
The Indonesian tourism industry explores its cultural wealth through the concept of village tourism, a potential that reflects the beauty and authenticity of the local community's life. As a concrete example, Alamendah Village Tourism can leverage its tourism potential to enhance the local economy. Thus, in this context, the research focuses on analyzing how Alamendah Village Tourism recognizes the tourism potential that can improve the economic sustainability of the local community in Alamendah Village. The research employs qualitative research methods as it seeks to understand how Alamendah Village Tourism identifies the tourism potential in its village to enhance the economic sustainability of the local community in Alamendah Village. The results and discussions depict the tourism potential, which is the excellent and admirable human resources in Alamendah Village, creating strategic opportunities to strengthen the local economy with sustainability as the main focus. Therefore, sustainable development is not only about economic growth but also about a wise balance between economic benefits, environmental conservation, and the empowerment of the local community.